Use of robotic and automated systems in welding and restoration of parts - I. Zakharova; S. Shchetynin; V. Shchetynina; A. Zusin; I. Volenko (Machinery & Energetics, 2025)
The research was aimed at analysing the use of robotic systems in welding and surfacing processes of mechanical engineering to increase the productivity, accuracy, and economic efficiency of production operations. The study used methods of comparative analysis, economic analysis, and risk analysis to assess the effectiveness of implementing robotic systems in the welding process and investigate their impact on costs, product quality, and working conditions. Analysis of the effectiveness of implementing robotic technologies has shown that automation of these processes reduces the likelihood of defects in welds and surfaced coatings, ensuring stable quality at all stages of production. The use of robotic systems such as ABB IRB 6700 and Fanuc ARC Mate 100iD allowed achieving precise control over welding and surfacing parameters, in particular, temperature, material feed rate, and current. Robotic welding and surfacing systems, in particular, from Fronius, KUKA and YASKAWA, are actively used in the energy, metallurgy, nuclear and aviation industries to improve the accuracy, safety, and efficiency of production processes. The study included the development of energy-saving technology for surfacing rolls of rolling mills to improve their wear resistance and corrosion resistance using Tesla Weld SAW/MMA MZ 630 devices and the Tesla Weld R1 welding robotic arm to automate the process and ensure high quality of the deposited layer. It was noted that robotic systems can work with a wide range of materials, in particular aluminium, steel, and alloys, which expands the possibilities of using the technology in mechanical engineering. Due to the robotisation of welding and surfacing processes, a significant reduction in production costs is achieved, since the need for manual control and correction of the process is reduced. Automation allows surfacing on worn parts, which extends the service life of the equipment and reduces the cost of replacing it